Sodium-ion battery hard carbon negative electrode material and preparation method and application thereof
Through the modification method of alkali solution activation and sugar solution impregnation, combined with the two-stage high-temperature carbonization process, the existing problems of high requirements for hard carbon anode material modification process equipment and many reagents are solved, and the preparation of high-performance sodium ion battery hard carbon anode material is realized, which improves the specific capacity and cycle stability of the material.
Patent Information
- Application Number
- CN202411843185.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-04
AI Technical Summary
The existing sodium ion battery hard carbon anode material modification process has high requirements for equipment and reaction conditions, and uses many reagents, which is not conducive to large-scale industrial production and environmental protection.
The pre-carbonized material was modified by alkali solution activation and sugar solution impregnation to form a rich pore structure and reduce the specific surface area. The hard carbon negative electrode material of sodium ion battery was obtained by two-stage high-temperature carbonization.
The specific capacity of the material and the performance of the negative electrode material are improved, the specific capacity for the first charging can reach 309.35mAh/g, and the Coulomb efficiency can reach 89.03% in the first week. At the same time, the process conditions are simplified and production costs are reduced.
Smart Images

Figure CN119551672A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion battery electrode materials, and in particular to a sodium ion battery hard carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries continue to attract attention and research in areas such as electric vehicles and portable devices due to their advantages such as high energy density and long cycle life. However, due to the limited lithium resources and the high production cost of lithium-ion batteries, it is necessary to develop lower-cost, sustainable rechargeable batteries. Sodium resources are abundant and cheap, and sodium-ion batteries are considered to be the most competitive candidate for lithium-ion batteries. The development of low-cost, high reversible capacity and excellent cycle stability of sodium-ion battery negative electrode materials has become a difficulty in the industry.
[0003] Biomass hard carbon has attracted much attention due to its abundant sources, low cost, and environmental friendliness. Its conventional preparation process includes pretreatment, precarbonization, and high-temperature carbonization. There are many studies on the selection of biomass raw materials and carbonization process conditions, but the electrochemical performance of biomass hard carbon is still a long way from its commercialization. In order to further improve the performance of biomass hard carbon in sodium-ion batteries, the modification of hard carbon materials is currently a hot research direction. Modification methods include pretreatment, chemical impregnation, surface grafting, element doping, coating, etc.
[0004] CN116854075A discloses a chemically surface modified biomass hard carbon material and its preparation method. The biomass raw material is dried, crushed, and pre-carbonized, and then placed in an atmosphere plasma sintering furnace. After treatment, it is carbonized at high temperature. The pre-carbonized material is treated with a plasma reducing atmosphere to effectively reduce the oxygen-containing functional groups on the surface. On the one hand, it can improve the hydrophobicity of the surface of the hard carbon material, solve the problem of battery gas bulging during the charging and discharging process caused by the easy adsorption of water molecules by the surface hydrophilic groups, and on the other hand, it can reduce the irreversible adsorption of sodium ions during the first charging and discharging process. However, the use of plasma equipment has high requirements for modification and is expensive, which is not conducive to large-scale industrial production.
[0005] CN117383540A discloses a method of surface modification of biomass hard carbon using an organic solvent impregnation method to improve electrochemical performance. However, the implementation process involves organic reagents such as tris[2-(3-mercaptopropionyl)ethyl]isocyanurate, epichlorohydrin, and organic amines, which is not conducive to environmental protection and violates the original intention of reducing the cost of biomass hard carbon. Summary of the invention
[0006] The present invention provides a sodium ion battery hard carbon negative electrode material and a preparation method and application thereof, so as to solve the technical problems mentioned in the background technology that the existing biomass hard carbon negative electrode material modification process has high requirements on equipment and reaction conditions and uses a lot of reagents.
[0007] In order to solve the above technical problems, the technical solution proposed by the present invention is: A method for preparing a hard carbon negative electrode material for a sodium ion battery comprises the following steps: (1) Pre-carbonizing the biomass raw material under a protective atmosphere to obtain a pre-carbonized material; (2) grinding the pre-carbonized material to obtain a pre-carbonized powder, and sequentially subjecting the pre-carbonized powder to an alkali solution activation treatment and a sugar solution impregnation treatment to obtain a modified pre-carbonized powder; (3) Carbonizing the modified pre-carbonized powder at 1000-1300° C. in a nitrogen atmosphere to obtain the sodium ion battery hard carbon negative electrode material.
[0008] The design idea of the above technical solution is that the present invention first uses an alkaline solution to etch the carbon skeleton of the pre-carbonized material to form a sufficient number of open pore structures, and then uses high-temperature carbonization to promote the formation of closed pores, thereby forming a rich pore structure and increasing the material interlayer spacing while also reducing the material specific surface area. Compared with the existing modification methods, the process synthesis conditions of the present invention are easy to control and the operation is simple, which can effectively improve the specific capacity and negative electrode material performance of the final obtained material.
[0009] As a further preferred embodiment of the above technical solution, the specific operation of the alkaline solution activation treatment in step (2) is: immersing the pre-carbonized powder in an alkaline solution, mixing at 50-60°C for 4-6 hours, washing with water, and drying to obtain an alkali-activated pre-carbonized powder. By controlling the temperature and time of co-heating with the sodium hydroxide solution, the carbon skeleton is etched to form an open pore structure, and the reaction is mild, which will not cause the collapse of the carbon skeleton, resulting in pore collapse and irreversible damage to the structure.
[0010] As a further preferred embodiment of the above technical solution, the alkaline solution is a sodium hydroxide solution with a mass fraction of 10%, and the mass of the sodium hydroxide solution is 10 to 20 times the mass of the pre-carbonized powder.
[0011] As a further preferred embodiment of the above technical solution, a two-stage pre-carbonization operation is adopted in step (1), the temperature of the first stage pre-carbonization operation is 200-300°C, the time is 4-6 hours, and the temperature of the second stage pre-carbonization operation is 500-600°C, the time is 4-6 hours. The purpose of the two-stage pre-carbonization process is to remove moisture, impurities, etc. in the biomass raw materials, so that the organic matter undergoes a carbonization reaction, forms a stable carbonaceous structure, obtains higher conductivity, better mechanical stability, and improves the interface stability between the hard carbon negative electrode material and the electrolyte.
[0012] As a further preferred embodiment of the above technical solution, the sugar solution in step (2) is a starch solution with a mass fraction of 20%, the immersion time of the sugar solution is 4 to 6 hours, and during the immersion process, the mass of the starch solution is 10 to 20 times the mass of the pre-carbonized powder.
[0013] As a further preferred embodiment of the above technical solution, in step (2), the pre-carbonized material is subjected to grinding, pickling, water washing and drying treatment in sequence to obtain pre-carbonized powder; the pickling treatment is to mix and stir the ground pre-carbonized material with a dilute hydrochloric acid solution at 50-60°C for 4-6 hours; the mass concentration of the dilute hydrochloric acid is 12%, and the mass of the dilute hydrochloric acid solution is 10-20 times that of the pre-carbonized material. The purpose of pickling is to remove inorganic salt impurities, ash, etc. generated after pre-carbonization.
[0014] As a further preferred embodiment of the above technical solution, the drying temperature is 60-80° C. and the drying time is 12-24 hours.
[0015] As a further preferred embodiment of the above technical solution, in step (3), the pre-carbonized powder is subjected to two-stage high-temperature carbonization under a nitrogen atmosphere, firstly the modified pre-carbonized powder is heated to 600-800°C at a heating rate of 5°C / min, kept at this temperature for 2-4 hours, and then heated to 1000-1300°C (more preferably 1300°C) at a heating rate of 5°C / min and kept at this temperature for 2-4 hours. After the sugar solution is impregnated and coated, it is not suitable to be rapidly heated to a high temperature. Medium temperature first and then high temperature are conducive to the stable formation of the carbon structure and avoid melting and foaming.
[0016] As a further preferred embodiment of the above technical solution, the biomass material includes at least one of biomass shell materials, biomass wood materials and straw.
[0017] As a further preferred embodiment of the above technical solution, in step (1), the biomass material is first crushed, washed, dried, and then pre-carbonized.
[0018] Based on the same technical concept, the present invention also provides a hard carbon negative electrode material for a sodium ion battery, which is prepared by the preparation method described in the above technical solution.
[0019] Based on the same technical concept, the present invention also provides an application of a hard carbon negative electrode material for a sodium ion battery, wherein the hard carbon negative electrode material for a sodium ion battery is used to manufacture a sodium ion battery.
[0020] The present invention has the following beneficial effects: The preparation method of the sodium ion battery hard carbon negative electrode material of the present invention uses biomass with abundant resources, low price and green environmental protection as the raw material, adopts alkaline activation to form pores, does not involve other organic reagents, and controls the activation conditions to first form a rich pore structure on the surface of the material, improve the material interlayer spacing, and facilitate the storage of more sodium ions. Hard carbon coating is performed on the basis of pore formation to convert most of the open pores into closed pores, reduce the material specific surface area, and greatly improve the material specific capacity. The sodium ion battery hard carbon negative electrode material prepared by the preparation method of the present invention has a first charge specific capacity of up to 309.35mAh / g and a first week coulomb efficiency of up to 89.03%. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the SEM image of the hard carbon negative electrode material for the sodium ion battery of Example 1. DETAILED DESCRIPTION
[0022] The present invention will be described in detail below with reference to the accompanying drawings and embodiments, but the present invention can be implemented in many different ways as defined and covered by the claims.
[0023] Embodiment 1: The modified biomass hard carbon material for the negative electrode of the sodium ion battery of this embodiment, the preparation method thereof comprises the following steps: (1) Coconut shell was selected as the biomass raw material, and the coconut shell was crushed into particles with a size of about 2-10 mm. After being washed three times in deionized water, it was dried in a forced air drying oven at 100 °C for 24 h.
[0024] (2) The crushed coconut shell raw material particles are added to a rotary atmosphere furnace for two-stage carbonization. Nitrogen with a mass volume of more than 99.9% is continuously introduced into the rotary furnace. The rotation number of the rotary furnace is set to 1 rpm. The carbonization is carried out at 300°C for 5 h and at 600°C for 4 h. After the two-stage carbonization, coconut shell carbon is obtained.
[0025] (3) Mill the coconut shell carbon in a ball mill at 500 rpm for several hours until the particle size is 5-7 μm. Mix the milled coconut shell carbon with a 12 wt% dilute hydrochloric acid solution (the mass of the dilute hydrochloric acid solution is 10 times that of the coconut shell carbon), stir and wash in a 60°C constant temperature pot for 6 hours, then wash with deionized water until neutral and dry.
[0026] (4) Soak the coconut shell carbon obtained in step (3) in a 10 wt% sodium hydroxide solution (the mass of the sodium hydroxide solution is 20 times that of the coconut shell carbon), mix and stir in a 60°C constant temperature pot for 6 h, then wash with deionized water until neutral and dry.
[0027] (5) The alkali-activated coconut shell carbon obtained in step (4) is immersed in a starch solution with a mass fraction of 20 wt%, stirred and immersed for 6 h at room temperature (25° C.) (the mass of the starch solution is 10 times that of the alkali-activated coconut shell carbon), and dried in an oven to obtain modified pre-carbonized coconut shell carbon.
[0028] (6) Under an inert atmosphere, the modified pre-carbonized coconut shell carbon obtained in step (5) was subjected to two-stage carbonization in a tubular furnace, and nitrogen with a volume content of more than 99.9% was continuously introduced. The temperature was first raised to 800°C at a heating rate of 5°C / min and kept at that temperature for 2h, then the temperature was raised to 1300°C at a heating rate of 5°C / min and kept at that temperature for 4h, and finally cooled to room temperature to obtain the sodium ion battery hard carbon negative electrode material of this embodiment, named GXHC-1, whose SEM image is shown as follows Figure 1 shown.
[0029] GXHC-1 was used to prepare a button half-cell with metallic sodium as the counter electrode. The test data showed that the first charge specific capacity was 309.35 mAh / g and the first week coulombic efficiency was 89.03%.
[0030] Embodiment 2: The modified biomass hard carbon material for the negative electrode of the sodium ion battery of this embodiment, the preparation method thereof comprises the following steps: (1) Coconut shell was selected as the biomass raw material, and the coconut shell was crushed into particles with a size of about 2-10 mm. After being washed three times in deionized water, it was dried in a forced air drying oven at 100 °C for 24 h.
[0031] (2) The crushed coconut shell raw material particles are added to a rotary atmosphere furnace for two-stage carbonization. Nitrogen with a mass volume of more than 99.9% is continuously introduced into the rotary furnace. The rotation number of the rotary furnace is set to 1 rpm. The carbonization is carried out at 300°C for 5 h and at 600°C for 4 h. After the two-stage carbonization, coconut shell carbon is obtained.
[0032] (3) Mill the coconut shell carbon in a ball mill at 500 rpm for several hours until the particle size is 5-7 μm. Mix the milled coconut shell carbon with a 12 wt% dilute hydrochloric acid solution (the mass of the dilute hydrochloric acid solution is 10 times that of the coconut shell carbon), stir and wash in a 50°C constant temperature pot for 6 hours, then wash with deionized water until neutral and dry.
[0033] (4) Soak the coconut shell carbon obtained in step (3) in a 10 wt% sodium hydroxide solution (the mass of the sodium hydroxide solution is 20 times that of the coconut shell carbon), mix and stir in a 50°C constant temperature pot for 6 h, then wash with deionized water until neutral and dry.
[0034] (5) The alkali-activated coconut shell carbon obtained in step (4) is immersed in a starch solution with a mass fraction of 20 wt%, stirred and immersed for 6 h at room temperature (25° C.) (the mass of the starch solution is 10 times that of the alkali-activated coconut shell carbon), and dried in an oven to obtain modified pre-carbonized coconut shell carbon.
[0035] (6) Under an inert atmosphere, the modified pre-carbonized coconut shell carbon obtained in step (5) is subjected to two-stage carbonization in a tubular furnace, and nitrogen with a volume content of more than 99.9% is continuously introduced. The temperature is first increased to 800°C at a heating rate of 5°C / min and kept at this temperature for 2 hours, then the temperature is increased to 1200°C at a heating rate of 5°C / min and kept at this temperature for 2 hours, and finally cooled to room temperature to obtain a modified hard carbon material for a negative electrode of a sodium ion battery, which is named GXHC-2.
[0036] A button half-cell was prepared using metallic sodium as the counter electrode. Test data showed that the first charge specific capacity was 298.59 mAh / g and the first-week coulombic efficiency was 88.55%.
[0037] Embodiment 3: The modified biomass hard carbon material for the negative electrode of the sodium ion battery of this embodiment, the preparation method thereof comprises the following steps: (1) Coconut shell was selected as the biomass raw material, and the coconut shell was crushed into particles with a size of about 2-10 mm. After being washed three times in deionized water, it was dried in a forced air drying oven at 100 °C for 24 h.
[0038] (2) The crushed coconut shell raw material particles are added to a rotary atmosphere furnace for two-stage carbonization. Nitrogen with a mass volume of more than 99.9% is continuously introduced into the rotary furnace. The rotation number of the rotary furnace is set to 1 rpm. The carbonization is carried out at 300°C for 5 h and at 600°C for 4 h. After the two-stage carbonization, coconut shell carbon is obtained.
[0039] (3) Mill the coconut shell carbon in a ball mill at 500 rpm for several hours until the particle size is 5-7 μm. Mix the milled coconut shell carbon with a 12 wt% dilute hydrochloric acid solution (the mass of the dilute hydrochloric acid solution is 10 times that of the coconut shell carbon), stir and wash in a 60°C constant temperature pot for 6 hours, then wash with deionized water until neutral and dry.
[0040] (4) Soak the coconut shell carbon obtained in step (3) in a 10 wt% sodium hydroxide solution (the mass of the sodium hydroxide solution is 20 times that of the coconut shell carbon), mix and stir in a 60°C constant temperature pot for 6 h, then wash with deionized water until neutral and dry.
[0041] (5) The alkali-activated coconut shell carbon obtained in step (4) is immersed in a starch solution with a mass fraction of 20 wt%, stirred and immersed for 6 h at room temperature (25° C.) (the mass of the starch solution is 10 times that of the alkali-activated coconut shell carbon), and dried in an oven to obtain modified pre-carbonized coconut shell carbon.
[0042] (6) Under an inert atmosphere, the modified pre-carbonized coconut shell carbon obtained in step (5) is subjected to two-stage carbonization in a tubular furnace, and nitrogen with a volume content of more than 99.9% is continuously introduced. The temperature is first increased to 800°C at a heating rate of 5°C / min and kept at this temperature for 4 hours, then the temperature is increased to 1100°C at a heating rate of 5°C / min and kept at this temperature for 2 hours, and finally cooled to room temperature to obtain a modified hard carbon material for a negative electrode of a sodium ion battery, which is named GXHC-3.
[0043] A button-type half-cell was prepared using metallic sodium as the counter electrode. Test data showed that the first charge specific capacity was 209.01 mAh / g and the first-week coulombic efficiency was 80.71%.
[0044] Embodiment 4: The modified biomass hard carbon material for the negative electrode of the sodium ion battery of this embodiment, the preparation method thereof comprises the following steps: (1) Coconut shell was selected as the biomass raw material, and the coconut shell was crushed into particles with a size of about 2-10 mm. After being washed three times in deionized water, it was dried in a forced air drying oven at 100 °C for 24 h.
[0045] (2) The crushed coconut shell raw material particles are added to a rotary atmosphere furnace for two-stage carbonization. Nitrogen with a mass volume of more than 99.9% is continuously introduced into the rotary furnace. The rotation number of the rotary furnace is set to 1 rpm. The carbonization is carried out at 300°C for 5 h and at 600°C for 4 h. After the two-stage carbonization, coconut shell carbon is obtained.
[0046] (3) Mill the coconut shell carbon in a ball mill at 500 rpm for several hours until the particle size is 5-7 μm. Mix the milled coconut shell carbon with a 12 wt% dilute hydrochloric acid solution (the mass of the dilute hydrochloric acid solution is 10 times that of the coconut shell carbon), stir and wash in a 60°C constant temperature pot for 6 hours, then wash with deionized water until neutral and dry.
[0047] (4) Soak the coconut shell carbon obtained in step (3) in a 10 wt% sodium hydroxide solution (the mass of the sodium hydroxide solution is 20 times that of the coconut shell carbon), mix and stir in a 60°C constant temperature pot for 6 h, then wash with deionized water until neutral and dry.
[0048] (5) The alkali-activated coconut shell carbon obtained in step (4) is immersed in a starch solution with a mass fraction of 20 wt%, stirred and immersed for 6 h at room temperature (25° C.) (the mass of the starch solution is 10 times that of the alkali-activated coconut shell carbon), and dried in an oven to obtain modified pre-carbonized coconut shell carbon.
[0049] (6) Under an inert atmosphere, the modified pre-carbonized coconut shell carbon obtained in step (5) is subjected to two-stage carbonization in a tubular furnace, and nitrogen with a volume content of more than 99.9% is continuously introduced. The temperature is first increased to 800°C at a heating rate of 5°C / min and kept at that temperature for 4 hours, then the temperature is increased to 1000°C at a heating rate of 5°C / min and kept at that temperature for 2 hours, and finally cooled to room temperature to obtain a modified hard carbon material for a negative electrode of a sodium ion battery, which is named GXHC-4.
[0050] A button-type half-cell was prepared using metallic sodium as the counter electrode. Test data showed that the first charge specific capacity was 204.74 mAh / g and the first-week coulombic efficiency was 80.08%.
[0051] Comparative Example 1: The other conditions and operations of the negative electrode material preparation method of this comparative example are the same as those of Example 1, except that step (4) and step (5) are omitted.
[0052] The obtained negative electrode material was used to prepare a button half-cell with metallic sodium as the counter electrode. Test data showed that the first charge specific capacity was 278.89 mAh / g and the first week coulombic efficiency was 87.46%.
[0053] Comparative Example 2: The other conditions and operations of the negative electrode material preparation method of this comparative example are the same as those of Example 1, except that step (4) is omitted.
[0054] The obtained negative electrode material was used to prepare a button half-cell with metallic sodium as the counter electrode. Test data showed that the first charge specific capacity was 215.70 mAh / g and the first week coulombic efficiency was 81.56%.
[0055] Comparative Example 3: The other conditions and operations of the negative electrode material preparation method of this comparative example are the same as those of Example 1, except that step (5) is omitted.
[0056] The obtained negative electrode material was used to prepare a button half-cell with metallic sodium as the counter electrode. Test data showed that the first charge specific capacity was 148.10 mAh / g and the first week coulombic efficiency was 68.95%.
[0057] Table 1. Electrochemical properties of hard carbon materials in various examples and comparative examples
[0058] In summary, the specific surface area of the hard carbon negative electrode material for sodium ion batteries prepared by the above preparation method is 5~300 m 2 / g; the average pore size of the hard carbon negative electrode material for sodium ion batteries is about 2nm, and the pore volume is 0.01-0.05cm3 / g, indicating that the obtained hard carbon negative electrode material has a closed microporous structure; Figure 1The scanning electron microscope image of the biomass hard carbon material prepared in Example 1 is shown. It can be seen that there are many closed, unpenetrated holes in the material, and some pore structures are filled with particulate matter. A large number of literatures show that the closed pore structure is conducive to the infiltration of electrolytes and the shuttling of sodium ions. In summary, through the pore-making-melt coating-two-step carbonization method of the present invention, the pore regulation of biomass-based hard carbon materials is achieved. The modified biomass hard carbon material has excellent electrochemical properties, especially the significantly improved charge capacity, which further promotes the application of this hard carbon material in sodium ion batteries.
[0059] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. For those skilled in the art, improvements and changes obtained without departing from the technical concept of the present invention should also be regarded as the protection scope of the present invention.
[0060] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a hard carbon negative electrode material for a sodium ion battery, characterized in that: The following steps are involved: (1) Pre-carbonizing the biomass raw material under a protective atmosphere to obtain a pre-carbonized material; (2) grinding the pre-carbonized material to obtain a pre-carbonized powder, and sequentially subjecting the pre-carbonized powder to an alkali solution activation treatment and a sugar solution impregnation treatment to obtain a modified pre-carbonized powder; (3) Carbonizing the modified pre-carbonized powder at 1000-1300° C. in a nitrogen atmosphere to obtain the sodium ion battery hard carbon negative electrode material.
2. The method for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: The specific operation of the alkaline solution activation treatment in step (2) is: immersing the pre-carbonized powder in an alkaline solution, mixing at 50-60° C. for 4-6 hours, washing with water, and drying to obtain an alkali-activated pre-carbonized powder.
3. The method for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 2, characterized in that: The alkaline solution is a sodium hydroxide solution with a mass fraction of 10%, and the mass of the sodium hydroxide solution is 10 to 20 times the mass of the pre-carbonized powder.
4. The method for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: In step (1), a two-stage pre-carbonization operation is adopted, wherein the temperature of the first stage pre-carbonization operation is 200-300°C and the time is 4-6 hours, and the temperature of the second stage pre-carbonization operation is 500-600°C and the time is 4-6 hours.
5. The method for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: The sugar solution in step (2) is a starch solution with a mass fraction of 20%. The immersion time of the sugar solution is 4 to 6 hours. During the immersion process, the mass of the starch solution is 10 to 20 times the mass of the pre-carbonized powder.
6. The method for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 1, characterized in that: In step (2), the pre-carbonized material is sequentially ground, pickled, washed with water and dried to obtain a pre-carbonized powder; the pickling treatment is to mix and stir the ground pre-carbonized material with a dilute hydrochloric acid solution at 50-60° C. for 4-6 hours; the mass concentration of the dilute hydrochloric acid is 12%, and the mass of the dilute hydrochloric acid solution is 10-20 times that of the pre-carbonized material.
7. The method for preparing a hard carbon negative electrode material for a sodium ion battery according to claim 6, characterized in that: The drying temperature is 60-80°C and the drying time is 12-24h.
8. The method for preparing a hard carbon negative electrode material for a sodium ion battery according to any one of claims 1 to 6, characterized in that: In step (3), the pre-carbonized powder is subjected to two-stage high-temperature carbonization in a nitrogen atmosphere. The modified pre-carbonized powder is first heated to 600-800°C at a heating rate of 5°C / min and kept at this temperature for 2-4 hours. Then, the modified pre-carbonized powder is heated to 1000-1300°C at a heating rate of 5°C / min and kept at this temperature for 2-4 hours.
9. A hard carbon negative electrode material for a sodium ion battery, characterized in that: The method is prepared by the method according to any one of claims 1 to 8.
10. An application of a hard carbon negative electrode material for a sodium ion battery, characterized in that: The sodium ion battery hard carbon negative electrode material is used for making sodium ion batteries.
Citation Information
Patent Citations
Preparation method of high-rate modified biomass hard carbon material
CN117383540A